LEDs Lighting Arrangements for Underground Mines - Pratap Singh Yadav; Nitai Pal; Dheeraj Kumar; S. Vamsi Krishna (Institute of Advanced Engineering and Science, 2015)
Lighting condition is very critical to mine workers, since they completely depend upon visual indication. Effective lighting systems provide better visibility and contribute to improved safety, production, productivity and efficiency of equipments. This paper intended to present a simulation study of configurations for the uniform illumination over a rectangular-target surface (underground mine 26X4.8 m gallery) using power LEDs. This cost effective lighting involved different sets of arrangements of LEDs that provide a close uniform light level for given optimized parameters. The optimized values of the variables in the arrangements were obtained by the using of MATLAB functions for optimization toolbox. DOI: http://dx.doi.org/10.11591/telkomnika.v15i1.7969